Band Alignment Engineering in 2D Ferroelectric Van der Waals Heterostructures for All‐In‐One Optoelectronic Architecture - Lu, Yanan; Xie, Dabao; Zhang, Congmin; Cao, Dan; Chen, Xiaoshuang; Shu, Haibo (Advanced electronic materials, 2025)
2D van der Waals (vdW) heterostructures consisting of vertically stacking atomically thin semiconductors with different band structures provide a flexible platform to design integrated electronic and optoelectronic devices with multi‐functionalities. However, the realization of device multifunctionality requires the heterostructures with tunable band alignments. Here an efficient strategy is proposed by constructing 2D vdW ferroelectric semiconductor heterostructures composed of atomically thin ferroelectrics and semiconductors to achieve this goal. These calculated results indicate that the local built‐in electric field derived from the ferroelectric polarization can effectively modulate the band alignment of the heterostructures, leading to 36 potential band‐alignment transition pathways. Using SnS/In2Se3 vdW heterostructure as a prototype example, a reversible switching from high‐resistance to low‐resistance state is demonstrated by the band‐alignment transition from type‐II to type‐III driven by ferroelecric polarization switching, consequently leading to giant tunneling electroresistance (TER) ratio as high as 1012%. Moreover, the heterostructure with the momentum‐space matching band structure and in‐plane anisotropy exhibits broadband photoresponse from near‐infrared to ultraviolet regions and excellent polarization sensitivity with the dichroic ratio up to 10.3. The ferroelectric polarization‐dependent conductance state and photoresponse in the heterostructures make them large potential for the realization of all‐in‐one optoelectronic architecture in artificial vision system. An attractive strategy is proposed to regulate the band‐alignment type and band offset of 2D van der Waals heterostructures by the integration of atomically thin ferroelectrics and semiconductors. The 2D ferroelectric van der Waals heterostructures exhibit giant tunneling electroresistance ratio and broadband polarized photoresponse, which make them potential candidates to construct all‐in‐one optoelectronic architecture.